Legal protection of patients in traditional medicine in the city of surakarta according to act no. 8 of 1999 - Nanang Prabowo, Gunarto; Rizka, Rizka; Iksan, Muchammad (IHSA Institute, 2024)
Traditional medicine is a method of treatment or care using traditional procedures. Both rely on knowledge, experience and skills passed down from generation to generation based on local community traditions (custom). The aim of this research is to analyze consumer protection towards traditional medical practices in the city of Surakarta. This research employs empirical legal research method. The results of this research explain consumer protection in the Consumer Protection Act lies in consumer rights which must be fulfilled in the practice of traditional medicine. Apart from that, a clinical practice permit and drug distribution permit from BPOM must be in place. If there is negligence in the implementation of traditional medicine, civil legal action is taken through a lawsuit for unlawful acts or a lawsuit for default and penal legal action through a police report for alleged malpractice. Actions in the form of health services for traditional medicine must prioritize consumer protection in terms of the competence of therapists or doctors, practice permits, production permits and product distribution issued by BPOM and the Indonesian Health Service which aims to maintain patient security and safety.